Peripheral cemento-ossifying fibroma: Report of a recurrence case - Kunal Sah; Alka D Kale; Seema Hallikerimath; Sunira Chandra (Wolters Kluwer Medknow Publications, 2012)
Peripheral cemento-ossifying fibroma [PCOF] is a reactive gingival overgrowth occurring frequently in the maxillary anterior region in teenagers and young adults. Here, we report a case of POCF in a 13-year-old male, which was previously surgically excised and had recurred after a period of 9 months. PCOF should be considered in differential diagnosis of such reactive hyperplastic lesions originating from the gingiva. Hence, early diagnosis with proper surgical excision and aggressive curettage of the adjacent tissues are essential for prevention of recurrence.